Directional Antenna With Lightweight Metamaterial Reflector for UAV-Based Networks - Hideya So; Kazuki Maruta (IEEE Access)
The wireless relay network utilizing multiple Unmanned Aerial Vehicles (UAVs) has now been widely studied. Since the radio propagation in the UAV network is close to free space environment, co-channel interference to other UAVs and the ground station (GS) becomes a serious problem. Designing a directional and multiband antenna is quite effective against this issue; multiple metamaterial reflectors are our key solution. Meanwhile, the flight time of the UAV imposes a limitation on the payload weight including communication equipment. This paper proposes a directional antenna employing a lightweight metamaterial reflector to reduce the antenna weight. It is realized by the woodpile structure which consists of layers of dielectric rods with a stacking sequence. Making the hole in the center of each dielectric rod can reduce the woodpile reflector’s weight with maintaining the antenna radiation performance. The electromagnetic field simulation clarified the reflection characteristics by making the hole. Both simulative and experimental evaluations clarified that the proposed antenna has almost the same radiation characteristics as the conventional one while reducing its weight by 25%, which saves the power consumption by 12.5%.